2018
DOI: 10.1088/1361-6560/aac749
|View full text |Cite
|
Sign up to set email alerts
|

Assessing MR-linac radiotherapy robustness for anatomical changes in head and neck cancer

Abstract: The MR-Linac will provide excellent soft tissue contrast for on-treatment imaging. It is well known that the electron return effect (ERE) results in areas of increased and decreased dose at air/tissue boundaries, which can be compensated for in plan optimisation. However, anatomical changes may affect the quality of this compensation. In this paper we aim to quantify the interaction of anatomical changes with ERE in head and neck (H&N) cancer patients. Twenty patients treated with either 66 Gy or 60 Gy in 30 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
27
0
2
Order By: Relevance
“…The effect of the magnetic field during MRgRT on the dose deposition has been shown to be influenced by the magnetic field strength, the incident beam energy, the beam entrance angle, and the boundary shape . Studies show that clinically acceptable plans can be achieved with multiple beam configurations over the target, and it has even been suggested that dosimetric effects due to the magnetic field could be used to develop partial breast MRgRT treatments …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the magnetic field during MRgRT on the dose deposition has been shown to be influenced by the magnetic field strength, the incident beam energy, the beam entrance angle, and the boundary shape . Studies show that clinically acceptable plans can be achieved with multiple beam configurations over the target, and it has even been suggested that dosimetric effects due to the magnetic field could be used to develop partial breast MRgRT treatments …”
Section: Introductionmentioning
confidence: 99%
“…During this time, gas or air is likely to appear in or pass through OARs, which would create deviations from the adapted dose distributions. In head and neck cancer patients, dosimetric effects due to ERE when the sinus cavity fills or clears have been shown to be of potential clinical concern . As larger changes are expected in other regions of the body, such as the digestive track, work should be done to understand the dosimetric effects of unplanned gas appearing in OARs during MRgRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive planning for NPC patients has been shown to significantly reduce the dose to the ipsilateral parotid gland [64]. Chuter et al [65] showed that it was feasible for an MR-linear accelerator to utilize current off-line strategies for adaptive planning for head and neck cancers.…”
Section: Magnetic Resonance (Mr)-linear Acceleratormentioning
confidence: 99%
“…Today, advances in imaging technology in the treatment room enable the ability to visualize, at each treatment fraction, anatomical, and in some cases functional, the response of the tumor and normal tissue to treatment. [23][24][25][26][27][28][29][30][31] This has dramatically changed the scope of adaptive radiotherapy. In addition to the increasing use of MR imaging, advances in image reconstruction for CBCT imaging, enabling 4D CBCT, breath-hold CT, and artifact reduction, has advanced the use of CBCT for adaptive radiotherapy, enabling dose calculations, detection of anatomical response, and improved understanding of physiological motion.…”
Section: Changing Landscape Of In-room Imagingmentioning
confidence: 99%